(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the quality of life and degree of satisfaction of patients submitted to orthodontic-surgical treatment after orthognathic surgery. Methodology: thirty ortho-surgical patients responded two specific questionnaires (Portuguese versions) -one on quality of life (Orthognathic Quality of Life Questionnaire – OQLQ) and another on degree of satisfaction (Post-Surgical Patient Satisfaction Questionnaire - PSPSQ) - and responded to a form containing socioeconomic-educational data and post-surgical time. The associations between the independent (age, gender, civil status, educational level, family income and post-surgical time) and dependent variables (quality of life and degree of satisfaction) were submitted of the Mann-Whitney test (significance of 5%). Spearman correlation test (significance of 5%) was applied to analyze the relationship between the dependent variables. Results: The OQLQ had a mean of 16.17 (±19.17) and median of 12, characterizing the sample with a good quality of life profile. The PSPSQ obtained a mean of 26.6 (±1.99) and median of 27, evidencing a high degree of satisfaction after surgical treatment. There was a significant correlation between the OQLQ x PSPSQ of the moderate negative type (0.40 to 0.69) and there was no significant correlation between socioeconomic-educational variables and post-surgical time with OQLQ and PSPSQ. Conclusion: The study indicated that the high satisfaction with the surgical treatment is directly related to the good quality of life presented after the treatment, demonstrating the importance of the ortho-surgical treatment.